ADVANCES IN THE NEW OIL AND GAS INDUSTRY - Bekjonov Rozisher Soatmurodovich; Norinov Fakhriyor Kurbanovich (American Journals Publishing, 2024)
Kerosene is mainly obtained from refined oil. Kerosene and residual kerosene were loaded on carts and camels and sold in the markets of Central Asia, Afghanistan, China, to cotton processing factories in Tashkent, Andijan, Kokan, oil growers and residents. Oil residues were used as fuel in railway transport. Later, several mines were opened in the Fergana basin (in the fields of Yorkoton and Moylisoy near Chimyon), the Chimyon-Altiariq oil pipeline was built, and the oil refinery was expanded. During this period, Russian and foreign capital took full control over oil production, oil processing, and sale of oil products. In 1913, a total of 13 thousand tons of oil was extracted.
Keywords: Carbonate reservoirs, geologic model, waterflooding, kerosene Field , product, high oil viscosity